The Student’s Strategies in Speaking English - Muhammad Nurman; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
Speaking is one of the most important skills to learn when learning a new language. It is important to find the best teaching strategy to help students learn the material Many different ways to learn English can be used by students, and they need to be aware of this. The purpose of this study was to find out what strategies students use to learn English and to identify the factors that influence their choice of learning method. Participants in this study were students in the third semester of the English semester. The data was collected through questionnaires and interviews. The results show that English seminar students predominantly used learning strategies based on metacognitive, cognitive, and social influential strategies when learning to speak. Almost half of the students used taking notes (51.4%) as their most common strategy, while only (19.6%) of students used translating. On the other hand, the male student's strategy was cooperation (16.8%) and self-assertiveness. These learning strategies can be used to help the student achieve their learning goals.